Case Report: A Rare Case of Elderly-Onset Adult-Onset Still’s Disease in a Patient With Systemic Lupus Erythematosus - Hirooka, Yasuaki; Okuda, Saki; Sugiyama, Masafumi; Shiga, Toshihiko; Nozaki, Yuji; Kinoshita, Koji; Funauchi, Masanori; Matsumura, Itaru (Frontiers in Immunology, 2022)
The rare systemic inflammatory disorder 'adult-onset Still's disease (AOSD)' is characterized by recurrent fever, evanescent rash, arthralgia, and leukocytosis with neutrophilia. The Yamaguchi criteria are widely used to diagnose AOSD; these criteria can be used for diagnosis after a wide range of infectious, rheumatic, and neoplastic diseases have been excluded. AOSD generally does not overlap with other rheumatic diseases. We present the rare case of an 80-year-old Japanese woman who presented with arthralgia, fever, and skin rash during treatment for systemic lupus erythematosus (SLE), which was finally diagnosed as an overlap of AOSD. Blood tests revealed leukocytosis with neutrophilia, high C-reactive protein (CRP), and liver dysfunction. Her anti-ds-DNA antibody titer and serum complement titer were at the same level as before and remained stable. We suspected AOSD based on the high serum ferritin level but hesitated to diagnose AOSD because of the patient's SLE history. We measured serum interleukin (IL)-18; it was extremely high at 161,221 pg/mL, which was strongly suggestive of AOSD. We thus diagnosed AOSD complicated during the course of treatment for SLE. The patient's arthralgia and high CRP level persisted after we increased her oral prednisolone dose and added oral methotrexate, but her symptoms eventually improved with the addition of intravenous tocilizumab. We note that the presence of autoantibodies or other rheumatic diseases cannot be absolutely ruled out in the diagnosis of AOSD. Although high serum IL-18 levels are not specific for AOSD, the measurement of serum IL-18 may aid in the diagnosis of AOSD in similar rare cases.